Growing more food with less water: how can revitalizing Asia?s irrigation help? - Mukherji, Aditi; Facon, T.; David, S.; Chartres, Colin J. (2010)
Irrigation has always played a central role in the agrarian economy of Asia, from supporting famed hydraulic civilizations in the ancient past to spearheading Green Revolution in the 1960s and 1970s,. Asia accounts for 70% of the world?s irrigated area and is home to some of the oldest and largest irrigation schemes. While these irrigation schemes played an important role in ensuring food security for billions of people in the past, their current state of affairs leaves much to be desired. The purpose of this paper is analyze the current trends in irrigation in Asia and suggest ways and means for revitalizing irrigation for meeting our future food needs and fuelling agricultural growth. The paper recommends a five pronged approach for revitalizing Asia?s irrigation and provides region specific strategies for the same. The underlying principal of these multiple strategies is the belief that the public institutions at the heart of irrigation management in Asia need to give up comfortable rigidity and engage with individual users? needs and the demands placed by larger societal changes.